Pengaruh Lingkungan Kerja, Penghargaan Finansial, dan Pertimbangan Pasar Kerja Terhadap Pemilihan Karir Mahasiswa Akuntansi Sebagai Akuntan Publik (Studi Empiris pada Mahasiswa Akuntansi Universitas Islam Malang) - Putri, Venni Endina; Mawardi, M. Cholid; Sari, Arista Fauzi Kartika (Universitas Islam Malang, 2023)
This research aims to determine how the influence of work environment, financial rewards, and labor market considerations on accounting students' career choices as public accountants. This research is a type of quantitative research, using 141 students of the Islamic University of Malang Accounting Study Program class of 2019 as a sample in this study. The data was collected using a questionnaire utilizing Google Forms with a Likert scale, namely 1 strongly disagree, 2 disagree, 3 neutral, 4 agree, and 5 strongly agree. Based on the results of research on the Accounting study program students class of 2019, it was found that the work environment obtained a significance value of 0.000 <0.05, so H0 was rejected and H1a was accepted, the financial reward variable obtained a significance value of 0.001 <0.05, so H0 was rejected and H1b was accepted, the job market consideration variable obtained a significant value of 0.000< 0.05, H0 was rejected and H1c was accepted. Based on this explanation, it can be said that the work environment, and financial rewards, and the job market Considerations affect the career choice of accounting students as public accountants.Keywords: Work environment, financial rewards, labor market considerations, career selection of accounting students as public accountants.